Pro-Inflammatory Th1 and Th17 Cells Are Suppressed During Human Experimental Endotoxemia Whereas Anti-Inflammatory IL-10 Producing T-Cells Are Unaffected - Brinkhoff, Alexandra; Sieberichs, Annette; Engler, Harald; Dolff, Sebastian; Benson, Sven; Korth, Johannes; Schedlowski, Manfred; Kribben, Andreas; Witzke, Oliver; Wilde, Benjamin (Frontiers in Immunology, 2018)
Objective Sepsis is one of the leading causes of the deaths in hospitals. During sepsis, patients are exposed to endotoxemia, which may contribute to the dysregulation of the immune system frequently observed in sepsis. This dysregulation leads to impaired pro-inflammatory responses and may increase the risk for secondary infections in sepsis. The experimental human endotoxemia model is widely used as a model system to study the acute effects of endotoxemia. Under physiological circumstances, the immune system is tightly regulated. Effector T-cells exert pro-inflammatory function and are restrained by regulatory T-cells (Tregs), which modulate pro-inflammatory effector responses. Endotoxemia may induce inadequate Treg activity or render effector T-cells dysfunctional. It was the aim of the study to investigate effector T-cell and Treg responses in an experimental human endotoxemia model. Methods In a cross-over designed placebo-controlled study, 20 healthy male volunteers received an intravenous injection of either lipopolysaccharide (LPS) (0.8 ng/kg body weight) or a placebo (saline 0.9%). CD3+ T-cells, CD4+ T-cells, CD8+ T-cells, and intracellular cytokine profiles were measured with flow cytometry at baseline and at repeated points after LPS/placebo injection. Complete blood cell counts were obtained with an automated hematology analyzer and cytokines were quantified by ELISA. Results Circulating neutrophils were significantly increased 2 h after LPS injection (p < 0.001) while absolute number of CD3+ T-cells, CD4+ T-cells, and CD8+ T-cells decreased (p < 0.001). Effector T-helper-cells (THs) showed a significant—but transient—decrease of pro-inflammatory IFNγ, interleukin (IL)-2, TNFα, and IL-17A production after LPS injection (p < 0.001). In contrast, the frequency of Treg and the capacity to produce IL-10 were unchanged (p = 0.21). Conclusion Effector THs fail to produce pro-inflammatory Th1-/Th17-associated cytokines after LPS challenge. In contrast, IL-10 production by Treg is not affected. Thus, endotoxemia-induced suppression of pro-inflammatory THs might be considered as a contributing factor to immunoparalysis in sepsis.